AN INVESTIGATION OF THE COMBINED INFLUENCE OF NEUROTICISM AND EXTRAVERSION ON ACADEMIC PERFORMANCE AMONG FRESH ENTRANTS TO PROFESSIONAL COLLEGE. - Neera Kumari (Student's Journal of Health Research, 2023)
Background:  It has been proposed that personality qualities, specifically neuroticism, and extraversion, have an impact on college students' academic success. Gaining knowledge about how these characteristics interact and affect academic performance might help students succeed. The purpose of this study was to look at how new students' academic performance at a medical college in East India is impacted by their combination of neuroticism and extraversion qualities. Methods:  Zung's self-rated Anxiety and Depression Scales were used to evaluate the psychomorbidity of 110 enrolled participants from the professional college. Costa and McCrae's tool, the NEO-FFI, was used to assess personality traits. Four exams in a row were used to gauge academic performance, allowing us to distinguish between high and low achievers. To investigate the connections between psychomorbidity, academic achievement, and personality factors, statistical analyses were carried out. Results:  The personality trait combination of low neuroticism and low extraversion (sometimes called "low-keyed") was found to be associated with significantly better academic performance among mentally healthy students than high neuroticism and high extraversion (often called "overly emotional"). Significantly, depressive pupils performed worse academically than their friends who were not depressed; this difference was especially noticeable in low-key people and positive optimists (low Neuroticism and high Extraversion). Conclusion:  The study's findings indicate that having a combination of low neuroticism and introversion is essential for achieving good academic proficiency on exams. Additionally, the study's findings were reviewed about the applicability of Gray's Behavioral Activation System/Behavioral Inhibition System (BAS/BIS) concept in the context of depression genesis. These understandings of the relationship between personality types and academic achievement can help develop instructional plans and resources for college students. Recommendation:  This study recommends that students should be enlightened on the various variables and how they contribute to their academic performance.